A study on the effectiveness of telemedicine on health outcome among Malaysians - Tan, Sue Rynn; Lai, Yan Xin; Heng, Joan Ka Yee; Chai, Yee Ling; Boo, Shi Qi (2024)
The provision of telemedicine services through telecommunications technology has become a transformative solution in the field of healthcare delivery. In the case of Malaysia, where disparities in access to healthcare persist, telemedicine is expected to improve health outcomes in both urban and rural settings. However, understanding its effectiveness requires examining a variety of factors, including patient satisfaction, accessibility to patient outcomes, and barriers faced by telemedicine users. This study aimed to investigate the effectiveness of telemedicine on health outcomes for Malaysians, focusing on patient satisfaction, auxiliary functions, and barriers to adopting telemedicine. With a hybrid approach, quantitative data on patient health outcomes into the patient experience is collected. Preliminary findings suggest a positive correlation between patient satisfaction and telemedicine effectiveness, underscoring the importance of user experience in healthcare delivery. In addition, assistive features such as remote patient monitoring and real-time interactive services play a vital role in improving patient outcomes and care coordination. However, barriers to the adoption of telemedicine, including technical limitations and privacy concerns, have prevented its widespread implementation. By addressing these barriers and leveraging the benefits of telemedicine, Malaysia can improve the accessibility and quality of healthcare services, especially for underserved populations. This research adds to a growing body of knowledge on the role of telemedicine in healthcare transformation, providing insights for policymakers, healthcare providers, and technology developers. Keywords: Telemedicine, Health Outcome, Patient Satisfaction, Auxiliary Functions, Barriers, Malaysia